ART AND CULTURE LEARNING MODEL FOR MUSIC ART MATERIAL USING SMARTPHONE MUSIC APPLICATIONS - Khairi, Ilhamul; Minawati, Rosta; Mulyadi (PT. Antis International Publisher, 2024)
Objective: This study explores the role of smartphones in the development of education in Indonesia, with a particular focus on how technology enhances the quality and efficiency of the learning process. The research aims to examine how smartphone applications can be utilized as innovative, interactive, and efficient learning tools in the educational context. Method: A comprehensive review of various smartphone applications available on the Playstore, including music and instrument-related apps, was conducted to analyze their potential for improving educational methods. The study also explores how these applications can be integrated into the existing curriculum to support a new and more effective learning model. Results: The integration of smartphones in education provides significant opportunities for enhancing learning. With a wide range of applications available, such as music instruments, string, piano, percussion, and organ apps, smartphones can function as versatile tools for creating innovative and interactive learning experiences. These applications can support students in engaging with subjects in a more hands-on and efficient manner, contributing to the overall improvement of education. Novelty: This research highlights the potential of smartphones as powerful tools for transforming education in Indonesia. By leveraging mobile technology, the study provides insights into how smartphones can be incorporated into the learning process to create a more dynamic and engaging educational environment. The findings also underscore the importance of adapting to technological advancements in order to meet the evolving needs of modern education.